Criar laços para viver juntos: a constituição de famílias entre os escravos de Vitória, 1850-1871 - Faria, Rosani Freitas (2013)
The following dissertation discuss the establishment of the family relations among slaves in the city of Vitória, the current principal city of the Espírito Santo Province, between 1850 and 1871. It was a region dedicated to the internal supply and characterized by the existence of small and medium set of slaves, which substitution occurred mainly by the sexual reproduction way. In this context, the slave family is analyzed in its multiple views, beyond the relations by blood, including the parental bonds established by the matrimony and the Christian cronyism. Also, the universe that surrounded the illicit relationships (constituted by the not follow of the ecclesiastics rules) was comprehended as built in the everyday coexistence among slaves, poor free man and even formal slave owners. By one hand, the matrimony was the main tool to weave alliances inside the captivity; by the other, the cronyism allowed slaves to spread its solidarity bonds outside the place they occupied. It included even slaves from other owners, emancipated and free men. For those couple marked by social and racial inequality, the development of relative and sexual relationships constituted the base of the illegitimacy. The attitude of the formal slave owners about its captive – specially what concern the family ties – is analyzed in a very peculiar moment: facing the death. The family stability is discussed and realized through monitoring the destiny of the slave family after the death of the formal slave owner and the consequent share of properties. The sources of this research are constituted fundamentally of post-mortem inventories, wills, ecclesiastic’s registrations (Baptism, marriage and death certificate), pastoral visit notes and reports from the province. The sources were used to comprehend the strategies and the social relationships with the purpose to build better conditions of existence.